Estimating a national critical mineral security index in Indonesia using analytical hierarchy process - Nyayu Aisyah; Nugroho Adi Sasongko; Yoyon Wahyono; Martin Anda; Allan Trench (Environmental and Sustainability Indicators)
Critical minerals are key to guaranteeing energy security and economic stability in a nation. Indonesia, as the largest country in Southeast Asia, has significant reserves of critical minerals. The current circumstances, however, pose substantial challenges for Indonesia as it strives for self-sufficiency in various sectors. Indonesia must pay attention to its natural resource management, especially that of critical minerals. This study aims to present information on securing critical mineral resources in Indonesia by constructing a Critical Mineral Security Index (CMSI). This study used a quasi-qualitative method, wherein the Analytical Hierarchy Process (AHP) was used as the process of analysis. A total of four dimensions have been proposed in this study—availability, accessibility, technology-efficiency, and environmental, social, and governance (ESG) dimensions with a total of 29 indicators. The results of the AHP confirm that the security level of critical mineral resources in Indonesia is 5.57. The results indicate that the availability dimension has the highest weight compared to the other dimensions, equal to 47.6%. While the accessibility dimension has the lowest level of resistance. The government should, therefore, prioritize improving the indicators of accessibility dimensions. These results have policy implications for the energy and mineral sector in the future, to further reinforce energy and mineral security on a national scale, which may ultimately support transition energy in Indonesia and strengthen national defense.